Analisis Perlakuan Akuntansi Aset Tetap Berdasarkan PSAK 216 di Yayasan RMS - Roby Renaldo; Irawan Irawan; Arif Makhsun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the accounting treatment of fixed assets in non-profit entities, a case study at the RMS Foundation and to determine the suitability of the accounting treatment that has been applied based on PSAK 216 dated 1 January 2024. The method used in this research is a qualitative method to find out in depth the treatment. fixed asset accounting at the RMS Foundation. The data collection technique in this research uses triangulation techniques, namely researchers collect data using different data collection techniques to obtain data from the same data source. The data collection techniques used were interviews, observation and documentation. The data analysis technique uses the Miles and Huberman model by carrying out data collection, data reduction, data display, and drawing/verification. The results of this research are that there is conformity regarding the accounting treatment of fixed assets at the RMS Foundation and there are some that have not been implemented. Appropriate accounting treatment is recognition, measurement upon recognition, measurement after recognition, and presentation of fixed assets. The accounting treatment for fixed assets that has not been implemented is termination and disclosure.